2010
DOI: 10.1186/1476-4598-9-170
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic repression of ROR2 has a Wnt-mediated, pro-tumourigenic role in colon cancer

Abstract: BackgroundWnt factors control cell differentiation through semi-independent molecular cascades known as the β-catenin-dependent (canonical) and -independent (non-canonical) Wnt signalling pathways. Genetic and epigenetic alteration of components of the canonical Wnt signalling pathway is one of the primary mechanisms underlying colon cancer. Despite increasing evidence of the role of the non-canonical pathways in tumourigenesis, however, the underlying molecular mechanisms are poorly understood.ResultsHere we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 26 publications
8
75
0
Order By: Relevance
“…This result is consistent with previous reports showing that ROR2 mRNA is highly upregulated in cancer cell lines [31,36]. To further confirm this analysis, TMAs were constructed using primary CRC specimens.…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with previous reports showing that ROR2 mRNA is highly upregulated in cancer cell lines [31,36]. To further confirm this analysis, TMAs were constructed using primary CRC specimens.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, it has been demonstrated that Pax6 regulates the expression of the alternatively spliced isoforms of Tnc (von Holst et al, 2007). The Wnt signaling pathway constitutes an additional cascade regulating cell cycle progression, proliferation, apoptosis and differentiation of retinal precursor cells in a stage-dependent manner (Lara et al, 2010). Another investigated effector was the neurogenic basic helix-loophelix (bHLH) transcription factor Mash1, which is expressed by retinal precursor cells and is involved in cell fate specification (Akagi et al, 2004).…”
Section: Tenascin C Is Involved In Neurogenesis During Retinal Develomentioning
confidence: 99%
“…Investigations of a Tnc À / À mouse strain (Forsberg et al, 1996;Saga et al, 1992) revealed subtle alterations in non-neural and neural tissues, resulting in several neurological defects, inhibition of regeneration/plasticity and de-regulated morphogenesis (Evers et al, 2002;Faissner, 1997;Fukamauchi et al, 1996;Fukamauchi et al, 1997;Garcion et al, 2004;Irintchev et al, 2005;Jones and Jones, 2000a). Immunohistochemical analysis revealed that Tnc is expressed in the retina in a spatiotemporal pattern (Klausmeyer et al, 2007;Lara et al, 2010). Investigations concerning the influence of Tnc during retinogenesis remained an outstanding question.…”
Section: Introductionmentioning
confidence: 97%
“…Regulation of specific genes in a subset of regulatory pathways has been identified to be disrupted in pancreatic cancer and modulated by dietary agents (78). These pathways involve apoptosis, DNA damage control, K-ras signaling, JNK signalings, invasion, Hedgehog signaling, Wnt-Notch signaling, TGF-ß, and regulation of the G1/S phase transition (79)(80)(81). The dietary agent curumin, a yellow spice found in both turmeric and curry powder, inhibits JNK, COX2, NF-kappaB, STAT3 and AP-1 activation (82) through epigenetic mechanisms.…”
Section: Nutrigenomics and Epigenetic Regulation Of Signaling Pathwaysmentioning
confidence: 99%